"Are You Willing to Die for This Work?" Public Targeted Online Harassment in Higher Education: SWS Presidential Address. Issue 3 (June 2018) - Ferber, Abby L.
This address examines a growing problem in academia: the public targeted online harassment of faculty. This harassment, organized and carried out by the alt-right and supported by other sectors of the right wing across the spectrum from mainstream to extreme, are intended to silence faculty and censor the curriculum. I examine a range of contextual factors that have facilitated this phenomenon, and discuss the experiences of seven other people, as well as myself, all with connections to higher education, that have experienced this unique form of attack. These conversations provide insight into the patterns evident in the form of the attack, individual and university responses, and informed the creation of lists of recommendations for those experiencing, preparing, and responding to attacks.